Exploration of Thermodynamics Concept of Madura Klampar Written Batik: Integration of Culture and STEAM-Based Education - Ayu, Hena Dian; Damayanti, Infa; Sundaygara, Chandra (Jurnal Ilmiah Pendidikan Fisika, 2025)
This research explores the concept of thermodynamics in making Klampar Madura batik, integrated with culture and education based on STEAM (Science, Technology, Engineering, Art, and Mathematics). Klampar batik, has a manufacturing process that involves thermodynamic concepts, such as changes in form and heat transfer. Thermodynamics is often considered an abstract and difficult subject for students to understand. The STEAM education approach offers a more engaging and applicable learning method, making thermodynamic concepts easier to grasp as they become more contextual. The research method used is descriptive qualitative with a cultural studies approach. Data collection techniques were conducted through interviews, observation, documentation, and literature study. The research results reveal that making Klampar batik involves the concept of thermodynamics at the stages of melting wax, fixation, and drying. Integration of physics concepts with culture and STEAM education, which includes Science (thermodynamics), Technology (canting design), Engineering (fabric, biron wax, canting), Arts (motifs), and Mathematics (thermodynamics in the fixation process). Through the STEAM cultural and educational approach, the batik process is a means to create works of art and preserve culture with a cross-disciplinary, knowledge-based approach.